The structure of dental procedures under general anaesthesia in children and adolescents with epilepsy - Tkaczuk-Płocica, Małgorzata; Szymańska, Jolanta; Rosiak, Joanna (Polish Journal of Public Health, 2014)
Introduction. One of the indications for dental treatment in general anaesthesia of children and adolescents is the patients’ refusal to cooperate with the dentist; this concerns especially the so-called special care patients, and among them, those suffering from epilepsy. Aim. The aim of the study was to evaluate the structure of treatment procedures in conservative dentistry and dental surgery performed under general anaesthesia in children and adolescents with epilepsy. Material and methods. The analysis covered case histories of 109 patients with epilepsy, aged 3-18 years, who received dental treatment under general anaesthesia. The patients were divided into three age groups, according to the dentition type: patients with deciduous dentition – 3-5 years of age; with mixed dentition – 6-12 years, and with permanent dentition – 13-18 years. The analysis concerned the procedures on both deciduous and permanent teeth. Results. An average number of extractions in a child with full deciduous dentition was 3.9 teeth, while in a child with mixed dentition – 2.7 teeth. The greatest number of deciduous teeth extractions concerned first and second molars. Carious cavities in the occlusal surfaces of permanent teeth, due to deep caries, were the most frequently treated lesions. Conclusions. In patients with epilepsy treated under general anaesthesia, extensive treatment needs, resulting from prophylactic and therapeutic neglect in dental care, were found. Conservative and surgical treatment, combined with prophylactic procedures, performed under general anaesthesia seems one of the necessary elements of a complex dental care in uncooperative children and adolescents.